DNA Metabarcoding Improves the Taxonomic Resolution of Visually Determined Diet Composition of Beaked Redfish (Sebastes sp.) - Sarah Brown‐Vuillemin; Louis Bernatchez; Eric Normandeau; Cecilia Hernandez; Denis Chabot; Réjean Tremblay; Pascal Sirois; Claude Nozères; Dominique Robert (Environmental DNA)
ABSTRACT Beaked redfishes (Sebastes fasciatus and Sebastes mentella) of the northwest Atlantic have recently reached record abundance levels in the estuary and northern Gulf of St. Lawrence, dominated by Sebastes mentella. Knowledge of their diet composition is essential to understand the trophic role that these groundfish play in the ecosystem. The objective of the present study was to compare the performance of visual examination and DNA metabarcoding of stomach contents of the same individual redfish caught in the estuary and northern Gulf of St. Lawrence. Using a universal metazoan mitochondrial cytochrome c oxidase subunit I (COI) marker, we identified a total of 24 taxonomic groups, composed of 22 species and two genera in the content of 185 stomachs with DNA metabarcoding. We compared these results to the 25 prey types, eight identified at the genus and nine at the species level, obtained with visual stomach content analysis (SCA). While both techniques revealed a similar diet composition, our results showed that the SCA and DNA metabarcoding perform differently for particular prey categories, both in terms of detectability and taxonomic resolution, as well as in the estimated relative importance of weight and occurrence in the diet. The use of DNA metabarcoding along with SCA validates and improves the taxonomic resolution of visually determined prey, which supports the concept that both techniques provide useful complementary information on the diet of redfish and likely other fish species.